The Way Through the Human-Shaped Snow - Saul Myers (Studies in 20th & 21st Century Literature, 1987)
This essay interprets Paul Celan's "Weggebeizt" as a concentrated recasting of major themes in the Book of Job. It attempts to show how the poet may have constructed the poem out of a close interrogation of passages in Job, including glosses and cryptic translations of the idiosyncratic Hebrew text. Talk of biblical "echoes" or "influences" is eschewed in favor of a method of parallel reading by which Celan's new-forged words are referred back to key words and phrases in the argument between Job and God. The main points of contact between Job and "Weggebeizt" are: 1) conflation of multiple and opposing senses of a single wind figure; 2) the recurring theme of trial and the ambivalent treatment of "true" and "false" witness as well as oaths of purity and true speech; other points of contact are: 3) ice and snow figures, 4) references to Sheol and heaven (which Celan combines into a single place). Some familiarity with the Book of Job is assumed, but key Hebrew words are cited with their alternate translations, especially when it appears that the poem is playing off multiple senses of the original. The paper is written in a commentary style, with line by line explorations of meaning.
Keywords: Paul Celan; Weggebeizt; Book of Job; poet; Hebrew; Biblical; Sheol; heave; ice; snow; figure; line by line explorations; commentary style